Hubungan Antara Tingkat Spiritualitas Dengan Tingkat Kualitas Hidup Pada Pasien HIV/AIDS Di Yayasan Spirit Paramacitta Denpasar - I Gede Meyantara Eka Superkertia; Ika Widi Astuti; Made Pande Lilik Lestari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is a chronic sexually transmitted infection. HIV in addition to causing physical disorders, also can cause social disruption affects the patient's life. One approach that is often used in assisting patients who have long suffered from HIV/AIDS is through spiritual therapy. Spiritual therapies that do may indirectly increase the significance of spirituality patient about his illness. This study aims to determine the relationship between the level of spirituality with the level of quality of life in patients with HIV/AIDS in Yayasan Spirit Paramacitta Denpasar. This research was a cross sectional study conducted during one week. The sample consisted of 45 people were selected by purposive sampling. Data collected by using a questionnaire of spiritual and quality of life to determine the level of spirituality and level of quality of life of respondents. Based on Spearman Rank test showed p=0,000 means that there were a correlation between the level of spirituality with the level of quality of life of patients with HIV/AIDS. With the r value = 0,829. Based on these, foundation or LSM suggested to be more intensive in providing spiritual care for people with HIV so that their quality of life will be better.